The behavioural and social sciences as hidden curriculum in UK dental education: A qualitative study. (20th September 2019) - Neville, Patricia; Zahra, Jez; Pilch, Katie; Jayawardena, Dasna; Waylen, Andrea
Abstract: Introduction: The behavioural and social sciences (BeSS) are an integral part of dental curricula, helping students become holistic, patient‐centred practitioners. Nevertheless, UK studies document that dental undergraduates struggle to see the relevance of BeSS to their training. Using the concept of hidden curriculum, this study explored dental studentsâ€™ perceptions of and attitudes towards BeSS in one dental school in the UK. Material and methods: Six focus groups were conducted with 37 dental students from years 1 to 5. Thematic analysis was conducted revealing five themes: student attitudes towards BeSS, teaching culture, learning culture, curricular issues and student culture. Results: Many students recognised how BeSS contributed to their communication and patient management skills. Nevertheless, the study revealed a dental student cohort who have a strained relationship with BeSS. This negative attitude became more apparent from year 3 onwards, when the clinical phase of studies begins. It was perpetuated and legitimated by the existence of a strong student culture that openly critiqued BeSS among and between student year groups. Discussion and conclusion(s): In UK dental education there is a hidden curriculum related to BeSS. By underestimating the utility of BeSS, students are failing to recognise the biopsychosocial dimensions relevant to oral health and dental practice. All UK dental schools should review their relationship with BeSS and assess whether they are perpetuating a hidden curriculum about BeSS within their curricula.